Key tools in the development of educational platforms "Up skills" (ADVANCED TECHNOLOGIES AND COMPUTER SCIENCE, 2022)
This research is aimed at developing unique software to eliminate the problem when choosingone or another platform for the implementation of this kind of educational services. When developingsoftware products, you never act on a whim - at least not unless you are planning business suicide. Thereis always a step-by-step plan that you follow to move from one stage to the next, making sure you don't slipas you move from idea to implementation. This article is an immersive overview of the softwaredevelopment process. As part of the product discovery process, it's all about connecting the dots betweenwhat you intend to build and whether or not someone will ever want you to use it. At this point, you shouldalready know enough why you are creating a product and who its end users are. But you need a morecoherent strategy to speed up the design process with your team. In addition to paid educational courseswith documentary evidence of learning outcomes, there are also opportunities for free online education.Educational programs involve several levels of training, different in duration and quality.
Keywords: Courses, video tutorials, trainings, gamification, distance learning, curator, programming, educational platform.